2020
DOI: 10.1038/s41598-020-72083-7
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte mitochondrial DNA copy number and built environment in Mexican Americans: a cross-sectional study

Abstract: Mitochondrial DNA (mtDNA) copy number in leukocytes has been regarded as a biomarker for various environmental exposures and chronic diseases. Our previous study showed that certain demographic factors (e.g. age, gender, BMI, etc.) significantly affect levels of leukocyte mtDNA copy number in Mexican Americans. However, the effect of the built environment on leukocyte mtDNA copy number has not been studied previously. In this cross-sectional study, we examined the association between multiple components of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Mexican Americans living in areas with a high density of roads had higher body mass index (BMI) than their counterparts 11 . We also observed that selected built environment factors (e.g., population density and road/intersection ratio) affect leukocyte mitochondrial DNA copy number levels, a biomarker linking environmental exposures and chronic diseases 12 .…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Mexican Americans living in areas with a high density of roads had higher body mass index (BMI) than their counterparts 11 . We also observed that selected built environment factors (e.g., population density and road/intersection ratio) affect leukocyte mitochondrial DNA copy number levels, a biomarker linking environmental exposures and chronic diseases 12 .…”
Section: Introductionmentioning
confidence: 71%
“…The data on built environment factors are presented in our previous publication 11 , 12 . In brief, to represent essential areas of the built environment, we assessed physical activity environment, land use variety, and food environment., Five exposure variables [population density (people per km 2 ), household density (households per km 2 ), road density (number of road links per km 2 ), and intersections density (number of road intersections per km 2 )] within a half-mile radius surrounding each participant's residence were included in the physical activity environment.…”
Section: Methodsmentioning
confidence: 99%
“…This investigation centered only on mtDNA CN and did not focus on additional elements that could impact on mitochondrial bioenergetics and disease, such as mtDNA haplotypes and sequence variation ( 84 , 85 ). The environmental and lifestyle determinants of mtDNA CN are poorly understood, with several factors being implicated ( 70 ). Importantly, statins have pleiotropic immunomodulatory effects and can negatively affect mitochondrial function and mtDNA CN ( 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies described the alterations only in mtDNA copy number in health and disease [ 64 69 ]; however, mtDNA alone is not enough indicative for the mitochondrial health evaluation. It is important to consider additional parameters such as mitochondrial enzymatic activities or modulations in bioenergetic pathways.…”
Section: Mhi and Bhi As Parameters To Quantify Mitochondrial Health I...mentioning
confidence: 99%